Style Features in Communication of the Crews With Mission Control - Yusupova, Anna; Shved, Dmitry; Gushin, Vadim; Chekalina, Angelina; Supolkina, Natalia (Frontiers in Neuroergonomics, 2021)
In "Content", an ISS Russian segment space experiment, features of communication between cosmonauts and Mission Control Center (MCC) were studied using content analysis. The method is based on concept of stress copings by Lazarus & Folkman. Differences found in cosmonauts’ communication led to assumptions about existence of individual communication styles in routine communication between cosmonauts and MCC. Found differences were defined using V. Satir’s classical model of communication types. Predominance of three main communication styles (“computing”, “blaming” and “placating”, as per Satir) was found. Manifestations and features of styles are discussed, considering effectiveness of “computing” style for ISS-MCC communication. Cosmonauts with a predominance of this communication style, mostly are stable and with good self-controlling. An increase of “blaming” and “placating” style features in cosmonauts’ communication may require adaptation of MCC communication and additional psychological support for the cosmonauts.